Visualisasi Data untuk Analisis Tren Penjualan Skincare dan Makeup Menggunakan Tableau - Mustika Sari, Wilda Aprilia; Voutama, Apriade (INTERNAL (Information System Journal), 2025)
The cosmetic industry has experienced rapid growth, particularly in the skincare and makeup sectors. With increasing competition, understanding sales trends has become a crucial factor for beauty businesses in developing effective marketing strategies. This study aims to analyze sales trends for skincare and makeup products using the Running Total method and monthly sales percentage changes, visualized through Tableau. The research data consists of product sales from various stores within the period of January 2023 to December 2024. The Running Total method is applied to analyze the cumulative sales pattern of skincare products, while monthly sales percentage changes are used to identify fluctuations in makeup product sales. The results indicate that skincare product sales show a stable growth trend, whereas makeup products exhibit more significant fluctuations. Factors such as promotional strategies, market trends, and seasonal effects significantly influence sales variations over different periods. These findings provide valuable insights for beauty businesses to optimize their marketing strategies, inventory management, and data-driven decision-making processes.